Fenomenologi Personal Branding Cosplayer: Studi Desain Komunikasi Visual dan Media Sosial - Chandra, Edy; Chandra, Nero Devanca (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Cosplay has evolved as both a form of identity expression and a personal branding strategy in the digital era. This study examines the phenomenology of cosplayer personal branding through a Visual Communication Design approach, highlighting the role of social media in identity formation and maintenance. This research is part of Edy Chandra's study entitled "Analysis of the Visualization of Indonesian Cosplayer Existence as a Potential for Branding Community Development, Entrepreneurship, and Creativity of Generation Z in Indonesia." Using a qualitative method comprising in-depth interviews, participatory observation, and content analysis, this research explores how Indonesian cosplayers construct their visual identity. Findings indicate that social media serves as a primary tool for shaping cosplayers' visual image, enhancing audience engagement, and fostering collaborations with communities and brands. Additionally, Visual Communication Design elements such as visual aesthetics, image composition, and digital storytelling contribute to effective personal branding. This study provides insights into how cosplayers strategically manage their identity through visual and digital approaches, offering valuable references for the creative industry and academia in understanding branding within the cosplay community.